Does the utilisation of new energy and waste gas resources contribute to product innovation from the perspective of a circular economy? Evidence from China - Ao, Xiangyuan; Teh, Boon Heng; Ong, Tze San; Muhammad, Haslinah; Selamat, Aslam Izah; Chen, Anqi (Frontiers in Energy Research, 2022)
These days energy-related enterprises started using a fancy terminology called circular economy (CE) to display their progress in opting for innovative approaches to mitigate carbon emissions and waste gas released in the enterprise during the operation. Hence, this paper examines whether there is any mediating role of innovation from a CE point of view or not in managing the waste resources and minimising the carbon emission on the innovation and quality of new energy products. For this, secondary data with a sample observation of 608 was selected from Chinese listed enterprises from 2015–2020. The empirical results revealed that the waste resource utilisation by firms is helpful to the quality of their products but does not significantly affect the innovation of their new energy products. In addition, the evidence from developing countries shows that companies’ carbon reduction behaviour benefits their new energy product innovation. However, it does not significantly impact the quality of their products. Model validation analyses the existence of corporate waste resource utilisation through corporate new energy product innovation, thereby contributing to corporate product quality. Overall, this paper facilitates enterprises’ new energy product development activities and fills the research gap between companies’ waste gas resource utilisation and new energy product innovation.